Material Requirements for Computer-Assisted Inquiry Models Development in Investment Assessment Learning - Ni Luh Gede Erni Sulindawati; Luh Indrayani; Made Arie Wahyuni (Universitas Pendidikan Ganesha, 2023)
In the current era of digital literacy, graduates are required to be able to compete in business while being able to overcome information technology problems. One way to increase student competency is by providing competency in selecting business decisions through the learning process. This research aims to identify the inquiry learning model material with the help of computer media. This type of research is qualitative. The method used in this research refers to Sugiono. The research subjects of this study were company managers, lecturers of financial management courses, validation experts regarding the content, appearance, and learning models developed, and accounting students who were taking financial management courses. The data analysis technique used is descriptive qualitative analysis. The results of this study identified the material of the computer-assisted inquiry learning model of investment assessment learning media, including the level of profit and risk, working capital and capital structure, as well as the cost of capital and capital structure. The method used is Payback Period, Average Rate of Return, Net Present Value, and Internal Rate of Return. The learning model that can be used is a computer-assisted inquiry learning model that contains inquiry learning model syntax, materials, worksheets, and power points.